“All Your, Our, Their Day-time Affairs […] Are Political Affairs”. On Social and Political Engagement in Contemporary Women’s Poetry on the Example of Post-December Poems - Grądziel-Wójcik, Joanna (Poznańskie Studia Slawistyczne, 2019)
An important, though underestimated theme in Polish poetry written by women is the thread of poetry engaged in social and political matters, thematizing the connection between literature and civic life. Poetesses are often accused of not rooting their works in history and of unwillingness to bring up current topics. Yet the problem is not the lack of interest in history and its political and social dimension, but the distinct way of its conceptualization, the relationship between the individual – though not always revealing its sex – subjective “I” in relation to history and challenges of its times. That is manifested, among others, in poems by Wisława Szymborska, Krystyna Miłobędzka, Bogusława Latawiec and Urszula Kozioł, which, to a different degree, exhibit the strategies of personalization, autobiographication, somatization and trivialization, characteristic of women’s poetry regarding the martial law period in Poland.